2011
DOI: 10.1021/jp207840q
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the 1-Hydroxyethyl-4-amino-1,2,4-triazolium Nitrate High-Energy Ionic Liquid System

Abstract: An investigation of the structure and dynamics of the high-energy ionic liquid, 1-hydroxyethyl-4-amino-1,2,4-triazolium nitrate (HEATN), was undertaken. Both experimental and computational methods were employed to understand the fundamental properties, characteristics, and behavior of HEATN. The charge separation, according to the electrostatic potential derived charges, was assessed. The MP2 (second-order perturbation theory) geometry optimizations find six dimer and five tetramer structures and allow one to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 87 publications
0
31
0
Order By: Relevance
“…By performing FMO/PCM geometry optimizations of the helical heparin oligosaccharides, Sawada et al 184 obtained an RMSD of 0.586 A ˚to experimental NMR structure and stressed the drawbacks of the force fields in the structure determination. Carlson et al 185 reported that FMO accurately predicted the relative energetics of several tetramers in ionic liquids.…”
Section: Molecular Clustersmentioning
confidence: 99%
“…By performing FMO/PCM geometry optimizations of the helical heparin oligosaccharides, Sawada et al 184 obtained an RMSD of 0.586 A ˚to experimental NMR structure and stressed the drawbacks of the force fields in the structure determination. Carlson et al 185 reported that FMO accurately predicted the relative energetics of several tetramers in ionic liquids.…”
Section: Molecular Clustersmentioning
confidence: 99%
“…The FMO method has been applied to proteins, [46][47][48] DNA, 49 and inorganic systems. [50][51][52][53] The FMO can be used for geometry optimizations, 54,55 transition state search 44 and MD simulations. [56][57][58] Full geometry optimizations of small proteins 54,59,60 and relatively short MD of chemical reactions 61,62 have been reported using FMO.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the FMO method has been applied to proteins, 52,53 DNA, 54 and inorganic systems. [55][56][57][58][59][60] The discussion in this work focuses on the three-body FMO method (FMO3) [61][62][63] combined with DFT. 64,65 The corresponding two-body FMO expressions can be easily obtained by ignoring the three-body correction terms.…”
Section: Introductionmentioning
confidence: 99%